2015
DOI: 10.1007/s13679-015-0153-z
|View full text |Cite
|
Sign up to set email alerts
|

Health Consequences of Weight Stigma: Implications for Obesity Prevention and Treatment

Abstract: Despite decades of research documenting consistent stigma and discrimination against individuals with obesity, weight stigma is rarely considered in obesity prevention and treatment efforts. In recent years, evidence has examined weight stigmatization as a unique contributor to negative health outcomes and behaviors that can promote and exacerbate obesity. This review summarizes findings from published studies within the past 4 years examining the relationship between weight stigma and maladaptive eating behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
313
1
20

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 423 publications
(374 citation statements)
references
References 76 publications
15
313
1
20
Order By: Relevance
“…Obesity is related to various poor health outcomes due to decreased physical and social functioning, and it is critical to understand these adverse outcomes in order to prevent them. Weightrelated stigma has serious negative effects on mental health, social functioning, and physical health [2]. Stigmatized individuals are often devaluing themselves, feeling helplessness, falling into despair, fearing rejection, and losing their self-confidence [3].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is related to various poor health outcomes due to decreased physical and social functioning, and it is critical to understand these adverse outcomes in order to prevent them. Weightrelated stigma has serious negative effects on mental health, social functioning, and physical health [2]. Stigmatized individuals are often devaluing themselves, feeling helplessness, falling into despair, fearing rejection, and losing their self-confidence [3].…”
Section: Introductionmentioning
confidence: 99%
“…2011; Schaefer and Simpkins 2014). Moreover, individual efforts to cope with and/or avoid weight‐related stigma often lead to less healthy behaviors associated with elevated chronic disease risk (Puhl and Suh 2015; Vartanian 2008). …”
mentioning
confidence: 99%
“…What is more, it shows weight reduction via lifestyle modification as achievable and "fun" when in fact research has confirmed that the exact opposite is true. That is, sustained weight loss through diet and exercise is nearly impossible (Weiss, Galuska, Khan, Gillespie & Serdula, 2007) and shame can result in worsened health among obese individuals and interferes with the success of weight loss interventions (Puhl & Suh, 2015, Rugseth, 2011. Nevertheless, frequent testing and weight screening persist as part of lifestyle-oriented programs in both public and private health care settings and there is little discussion of failure and shame in reference to such interventions (Dolezal, 2015).…”
Section: Introductionmentioning
confidence: 99%